Citizen Charter as Governance Reform Initiative for Quality Services - Kaphle, Sushmita (Journal of Productive Discourse, 2024)
The Citizen Charter (CC) is implemented to enhance the capabilities of local government in delivering services to people. It represents the official commitment to providing quality services to the public, and all service recipients need to have clear and concise information about the services and goods being provided. At the heart of the discussion on governance reform and the CC lies the question of whether public institutions foster the creation, dissemination, and processing of knowledge on the CC, which could ultimately lead to improved service delivery quality. Thus, this study examines the role of institutional factors such as procedural transparency and clarity, timely service delivery, and grievance handling systems in municipal service delivery post-implementation of the CC. The philosophical underpinning of this study adopts a pragmatic approach, utilizing a sequential explanatory mixed method. The findings reveal that there is increasing procedural transparency, and timely service delivery is gradually improving. However, the grievance handling system within the municipality still appears to be weak. It is evident from the study that the implementation of the Citizen Charter as a governance reform practice must address issues of reliability, responsiveness, and accuracy (RRA) to ensure quality service delivery (QSD) at the local level.